Pathologic complete response after Sintilimab combined with FOLFOX therapy in MSI-H type patients with locally advanced GC: a case report - Wang, Xiaoke; Gu, Yuanhui; Yi, Lin; Wu, Tao; Wang, Ling; Tian, Jiao; Lu, Yuyuan; Jin, Penghui; Yang, Xin; Yang, Yan (Frontiers in Oncology, 2025)
As one of the most common gastrointestinal tumors, Gastric Cancer (GC) poses a serious threat to human health due to its high morbidity and mortality. The current treatment strategy is a comprehensive treatment program mainly based on surgery, especially for advanced GC patients. The emergence of immune checkpoint inhibitors has completely changed this status quo, and the synergistic effect of neoadjuvant immunotherapy combined with chemotherapy has significantly improved the resection and radical rate and overall survival of patients with advanced local GC. We present a case of locally advanced GC (cT4N0Mx) with microsatellite instability high (MSI-H) and PD-L1 Combined Positive Score (CPS)=2. The patient received neoadjuvant therapy with Sintilimab combined with FOLFOX (folinic acid (leucovorin), 5-fluorouracil (5-FU), and oxaliplatin), and significantly reduced tumor volume after 3 cycles of treatment. Then she underwent subtotal gastrectomy with gastrojejunostomy and D2 lymph node dissection. The postoperative pathological results showed that no cancerous tissue remained in the tumor tissue, and pathologic complete response (pCR) was achieved. The first cycle of adjuvant therapy with the same protocol was received after surgery. During adjuvant therapy, patients mainly experienced side effects such as dyspepsia, nausea and mild myelosuppression. Therefore, immunotherapy with Sintilimab combined with FOLFOX chemotherapy has the potential to be an effective treatment option for patients with resectable locally advanced MSI-H GC.